A Comparison of Three Designs for List-style Open-ended Questions in Web Surveys. Issue 4 (November 2022) - Kunz, Tanja; Meitinger, Katharina
Although list-style open-ended questions generally help us gain deeper insights into respondents' thoughts, opinions, and behaviors, the quality of responses is often compromised. We tested a dynamic and a follow-up design to motivate respondents to give higher quality responses than with a static design, but without overburdening them. Our results showed that a follow-up design achieved longer responses with more themes and theme areas than a static design. In contrast, the dynamic design produced the shortest answers with the fewest themes and theme areas. No differences in item nonresponse and only minor differences in additional response burden were found among the three list-style designs. Our study shows that design features and timing are crucial to clarify the desired response format and motivate respondents to give high-quality answers to list-style open-ended questions.